2018
DOI: 10.1021/acs.jpcc.8b03512
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport Behavior in Solution-Grown Methylammonium Lead Tribromide Perovskite Single Crystal Using α Particles

Abstract: Methylammonium (MA) lead hybrid perovskite single crystal recently received attention as a potential radiation detection material. Here, we report the MAPbBr 3 bulk crystals grown by the modified antisolvent vapor-assisted crystallization method. The growth rate is determined by diluting the antisolvent, which results in the average size of MAPbBr 3 crystals to significantly increase from 2 × 2 × 1 to 15 × 15 × 5 mm 3 . The morphology evolution of MAPbBr 3 crystals, which is contributed by the growth anisotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 44 publications
(58 reference statements)
1
55
0
Order By: Relevance
“…A modified antisolvent vapor-assisted crystallization method was employed to grow MAPbBr 3 single crystals. 39 An equimolar mixture of the MABr (99.9%) and PbBr 2 (99.9%) was dissolved in dimethylformamide (DMF) for 30 min using magnetic stirring. The solution concentration was controlled in the range of 0.7−1.4 M. To control the MAPbBr 3 growth rate, the antisolvent mixture of dichloromethane and DMF was volatilized into the precursor solution to reduce the solubility of MAPbBr 3 in the solution.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…A modified antisolvent vapor-assisted crystallization method was employed to grow MAPbBr 3 single crystals. 39 An equimolar mixture of the MABr (99.9%) and PbBr 2 (99.9%) was dissolved in dimethylformamide (DMF) for 30 min using magnetic stirring. The solution concentration was controlled in the range of 0.7−1.4 M. To control the MAPbBr 3 growth rate, the antisolvent mixture of dichloromethane and DMF was volatilized into the precursor solution to reduce the solubility of MAPbBr 3 in the solution.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Since the important work of Kojima et al [1] in 2009 showing the power conversion efficiency (PCE) of around 3.81% for solid-state perovskite solar cells, organometallic halide perovskites (OMHPs) have experienced a remarkable development as highly efficient optoelectronic materials for a variety of applications particularly solar cells [2] , light emitting diodes [3] (LEDs) and photodetectors [4] . Recently, it has been shown by several groups that the outstanding intrinsic properties in OMHPs single crystals can empower a new generation of ionizing radiation sensors with remarkably high mobility-lifetime product [5,6] . One notable property of OMHPs is the lowtemperature solution growth, which is considerably lower than high-temperature melt growth techniques commonly used for classical inorganic semiconductors (e.g., Si, CdTe, GaAs, Ge, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…The large reduction in spin lifetime with increasing temperature has also been considered theoretically [66], where it is shown that τ sf may be reduced by over two orders of magnitude between 10 and 300 K. Thus, our obtained value of τ sf =189 ps for MAPbBr 3 at 300 K is eminently remarkable. Please note this estimated value could be larger since the dynamical spin injection method used in this paper, the spin lifetime may be reduced by coupling of the spins at the surface of the MAPbBr 3 single crystal to the adjacent NiFe layer [77,78].…”
Section: Discussionmentioning
confidence: 98%